The Economic Value of Tengkalang as a Transport Tool for Brondolan Palm Oil Based on Local Wisdom - Hartono, Hartono; Setyawan, Heri; Setiawan, Koko; Saloko, Subakho Aryo (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
Oil palm is agricultural that has excellent potential as a producer of vegetable oil globally, and oil palm plantations contribute to providing jobs for thousands of people in Indonesia. The greater a company, the more efficiency of work is needed. This research represents an effort to find a more efficient brondolanan transportation tool for workers in oil palm plantations. The study was conducted in May 2019 in two locations, the first location in Terusan Village, the second location in PT. Sinarmas, Manis Mata District, West Kalimantan. Data analysis uses descriptive analysis methods where the respondents of this study are employees of PT. Sinarmas as many as 30 people. The results showed that the utilization of tengkalang as a carrier brondolanan for workers in PT. Sinarmas is more effective and also more cost-effective. One unit has a lifespan of more than six months with a cost per unit of Rp. 20,000. While the black bucket per unit has a benefit period of three months with a cost per unit of Rp. 15,000. Then the result of cost analysis is calculated in one year, using tengkalang more efficiently by buying tengkalang Rp. 40.000 / year, while the black bucket purchase cost Rp. 60.000 / year. In addition, usingtengkalang means that the Company also participates in the welfare of surrounding communities to progress and grow together to improve the development of families and villages.